IMPLEMENTING GESTURES INTO VOCABULARY INSTRUCTION TO AID RECALL AND RETENTION - Emma Dilley (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This presentation will highlight the idea of incorporating gestures into vocabulary instruction to help the students recall and retain the new vocabulary words. I predict that with the incorporation of the strategy of gestures into instruction, kindergarten students will be able to retain more vocabulary words compared to vocabulary instruction that does not include gestures. The data being collected will be in the format of a pretest and posttest, paired with a teacher interview to see both the quantitative and qualitative sides of the study. The collection of previous relevant research will also be presented, as well as an analysis of the data collected.